Knockdown of Long Non-coding RNA SNGH3 by CRISPR-dCas9 Inhibits the Progression of Bladder Cancer - Cao, Yu; Hu, Qiong; Zhang, Ruiming; Li, Ling; Guo, Mingjuan; Wei, Huiling; Zhang, Li; Wang, Jianfeng; Li, Chunjing (Frontiers in Molecular Biosciences, 2021)
Recent study suggest that long non-coding RNAs （lncRNAs） play important roles in the development and progression of cancer. LncRNA SNGH3 （ small nucleolar RNA host gene 3 ） is overexpressed in multiple types of cancer, acting as an oncogene in cancer development. However, the clinical relationship and molecular mechanism of SNGH3 in bladder cancer (Bca) is still mysterious. In this study, we discovered that SNGH3 was significantly up-regulated in Bca tissues and cell lines. Furthermore, up-regulated SNGH3 expression was positively associated with TNM stage and histological grade of Bca. Further experiments confirmed that knockdown of SNGH3 using CRISPR-dCas9 inhibited cell proliferation and migration and induced cell apoptosis in Bca. In conclusions, these findings demonstrated that SNGH3 played an important regulatory role in Bca and may function as a potential diagnostic biomarker and therapeutic target.